Pembelajaran Sosiologi Pendidikan dengan Menggunakan Treatment Metode Training Sebagai Upaya Peningkatan Kecerdasan Spiritual Mahasiswa di Program Studi Pendidikan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Manado - Fathimah, Siti (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This research is expected to provide information about the use of the training method in increasing spiritual intelligence as well as to add to the data that the use of the training method in increasing spiritual intelligence is explained in a pleasant way and by giving examples. The research method used is Classroom Action Research (CAR). The findings of this study indicate that spiritual intelligence training activities can increase spiritual intelligence in students of the Sociology Education study program, Faculty of Social Sciences, Manado State University. The existence of training allows children to know what spiritual intelligence is, as well as anything that includes spiritual intelligence..